Air leakage and adherence to continuous positive airway pressure therapy in patients with moderate to severe obstruction sleep apnoea : a cross sectional study - Nadia Syafeera Naserrudin,; Abdullah Sani Mohamed,; Mawaddah Azman,; Mazlinda Mahadzir,; Norazmi Mohamad,; Marina Mat Baki, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This multicentre study aimed to evaluate the air leakage following a palatal surgery and its effect on CPAP adherence in OSA patients. The data on air leakage and adherence were objectively obtained and evaluated from the recorded CPAP therapy data. Forty patients were divided into two groups: surgery (18 patients) and non-surgery (22 patients). The mean air leakage level was 7.62±8.14% and 12.62±13.81% and mean adherence was 51.44±35.27% and 60.03±27.04% for surgery and non-surgery, respectively. There was no significant difference in CPAP adherence (p=0.389) but for mean air leakage it was significantly higher in non-surgery (p<0.01). The occurrence of significant air leakage during CPAP therapy was not associated with surgery (p=0.436). There was no association between poor CPAP adherence and surgery (p=0.622). In terms of impact of palatal surgery, it did not cause significant leakage with no significant association to poor adherence.